Environmental factors as correlates of accident occurrence among secondary school students in Lagelu Local Government Area of Oyo State (2015)
This study explores environmental factors as correlates of accident occurrence among secondary school students in Lagelu Local Government Area of Oyo State. The study adopted descriptive survey research design. Multi-stage sampling techniques were adopted to select five hundred (500) students and one hundred (100) teachers from all public secondary schools in the Local Government Area of Oyo State as respondents. A self- developed validated questionnaire titled ‘’Correlate of School Accident Questionnaire” (CSAQ) was used for data collection with reliability of r = 0.69.Four hypotheses were raised and the Data collected were analysed using Pearson Product Moment Correlation (PPMC) at 0.05 alpha level. The results showed that there were significant correlation between School location (close to the road, forest, bushy, stony and hilly areas); school playing grounds football field, Sport court and general playing area); School indoor environment (classrooms, library, laboratory and Home Economic Kitchen); and school structure (school building, floors, windows, stairs and doors) and accidents occurrence among secondary school students in Lagelu Local Government Area of Oyo State. Based on the findings, it was recommended that health and safety education should be organized for school administrators and teachers on the importance of safe school environment and strategies of school accident prevention. Secondary school students should also be taught personal safety.